Mortality in Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease with Lower and Higher Decaf Scores - Sara Daud, Asma Ambreen, Aisha Shafique, Shomaila Awan, Asma Sabir, Nabila Zaheer, Sara Daud, Asma Ambreen, Aisha Shafique, Shomaila Awan, Asma Sabir, Nabila Zaheer (Journal of Rawalpindi Medical College, 2022)
Background: To determine diagnostic accuracy of DECAF score in predicting mortality in patients with acute exacerbation of chronic obstructive pulmonary disease having DECAF score <4 and within 7 days of hospital admission keeping actual mortality as gold standard. Methods: In this cross sectional validation study, 146 Patients with COPD were selected from emergency and OPD of Fauji Foundation Hospital Rawalpindi presenting with signs and symptoms of acute exacerbation of COPD from 15 may 2017-15 Nov. 2017.The procedure began after taking informed consent of the patients. Clinical features documented and investigations were sent. The expense of all the tests was borne by the hospital administration and not the patient. A specially designed Performa was used for data collection. RESULTS: Mean age (years) in the study is 64.90+0.93. Patients with DECAF score of 1, 2 and 3 are (2.7+26+35.6 =64.3) are 64 %. The cases with DECAF score of 4 are 26.7% and the cases with DECAF score of 5 and 6 are 8.9%. DECAF score versus mortality with different age groups and duration of smoking gave reasonably high values of sensitivity and, specificity. Also the PPV and NPV values are appropriate. The minimum diagnostic accuracy is 71.23% indicating that this test is appropriate in predicting the true status of the cases. CONCLUSION: The study concludes that DECAF score is a useful predictor of mortality in patients admitted with acute exacerbation of COPD. Patients admitted in hospital with high DECAF score of should be admitted in intensive care unit because they may require invasive ventilation due to respiratory failure and high mortality. KEYWORDS: Chronic obstructive pulmonary disease, acute ex